A new species of the Miniopterus australis species complex (Chiroptera: Miniopteridae) from the Western Ghats, India - Srinivasulu, Bhargavi; Srinivasulu, Aditya (Zootaxa, 2023)
The genus Miniopterus is highly diverse in cryptic species. Based on integrated approaches of morphometrics, echolocation call analysis, and molecular phylogenetics, we present evidence of a hitherto undescribed species, Srini’s Bent-winged bat Miniopterus srinii sp. nov.. The new species, found in the Western Ghats of southern Karnataka, India, closely resembles the Small Bent-winged bat Miniopterus pusillus, found elsewhere in Karnataka, Kerala, and Tamil Nadu, India. Although it shows external similarity with Miniopterus pusillus sensu stricto from the Nicobar Islands, the new species is relatively larger and distinct in craniodental measurements and echolocation call parameters, despite slight overlaps. Importantly, Miniopterus srinii exhibits morphological convergence with Miniopterus pusillus as despite similarities in morphologies, there is a significant genetic distance of 10.84 ± 0.22%. The new cryptic species shares distribution with Miniopterus phillipsi and Miniopterus pusillus in the Western Ghats, further highlighting the need to study both the genus’ cryptic diversity, and the region’s conservation importance.